PENGARUH PENATAUSAHAAN BARANG MILIK DAERAH TERHADAP KUALITAS LAPORAN BAPPELITBANGDA KABUPATEN BANDUNG - Silvi Fitria; Khaerul Umam; Ai Siti Farida (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2022)
This study aims to determine whether there is an effect of the administration of regional property on the quality of the financial statements of Bappelitbangda Bandung Regency. Mahmudi stated that financial reports will be of high quality if they have the following characteristics: 1) relevant; 2) reliable; 3) comparable; and 4) understandable. In this study, the researcher used a quantitative approach with data sources coming from primary and secondary sources. Data collection techniques used by researchers are through observation, questionnaires and literature study. To support the research analysis, the researcher used descriptive statistics with the Statistical Product and Service Solutions (SPSS) program test tool. This study concludes that there is an influence on the administration of regional property on the financial quality of Bappelitbangda Bandung Regency. Through R square which shows the independent variable administration has a positive but not significant effect on the quality of financial reports, while the rest is influenced by other variables that were not investigated in this study.